X-ray magnetic circular dichroism in Co2FeGa: First-principles calculations - Kukusta, D.A.; Antonov, V.N.; Yaresko, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The electronic structure and x-ray magnetic circular dichroism (XMCD) spectra of the Heusler alloy Co2FeGa were investigated theoretically from first principles, using the fully relativistic Dirac linear MT-orbital (LMTO) band structure method. Densities of valence states, orbital and spin magnetic moments are analyzed and discussed. The origin of the XMCD spectra in the Co2FeGa compound is examined. The calculated results are compared with available experimental data.